2016
DOI: 10.1016/j.prnil.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer biomarkers: Are we hitting the mark?

Abstract: PurposeLocalised prostate cancer diagnosis and management is increasingly complex due to its heterogeneous progression and prognostic subgroups. Pitfalls in current screening and diagnosis have prompted the search for accurate and invasive molecular and genetic biomarkers for prostate cancer. Such tools may be able to distinguish clinically significant cancers from less aggressive variants to assist with prostate cancer risk stratification and guide decisions and healthcare algorithms. We aimed to provide a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 43 publications
1
67
0
1
Order By: Relevance
“…The 22‐gene Decipher predicts metastasis following RP (Erho et al ., 2013; Karnes et al ., 2013; Klein et al ., 2016). While these and other biomarkers assist decision making and thus improve patient management, their clinical application requires further validation (Lamy et al ., 2017; Martin, 2016; McGrath et al ., 2016; Patel and Gnanapragasam, 2016; Ross et al ., 2016; Zhuang and Johnson, 2016). There is a clear need to improve our ability to stratify PCs with high risk of recurrence following RP.…”
Section: Introductionmentioning
confidence: 99%
“…The 22‐gene Decipher predicts metastasis following RP (Erho et al ., 2013; Karnes et al ., 2013; Klein et al ., 2016). While these and other biomarkers assist decision making and thus improve patient management, their clinical application requires further validation (Lamy et al ., 2017; Martin, 2016; McGrath et al ., 2016; Patel and Gnanapragasam, 2016; Ross et al ., 2016; Zhuang and Johnson, 2016). There is a clear need to improve our ability to stratify PCs with high risk of recurrence following RP.…”
Section: Introductionmentioning
confidence: 99%
“…The 4K score test (Opko Health Inc.) includes the panel of 4 kallikrein proteins (fPSA, tPSA, iPSA, and hK2) plasma levels and has also been developed to differentiate between patients with aggressive PCa eligible for biopsy and those with low risk and benign lesions [33,34]. Similarly to PHI, the potential of kallikreins combination to improve detection specificity and thus reduce costs has…”
Section: K Score -Does More Mean Better?mentioning
confidence: 99%
“…Another technical problem of RNA instability has also been addressed recently, as RNA extraction efficiency can be potentially improved with novel RNA sequence-specific capture resulting in better sensitivity and specificity [43]. In a majority of studies performed with Progensa, PCA3 score of <25 implies low risk of PCa [34,[44][45][46]. The meta-analysis on multi-centre European prospective studies confirmed however that clinical aid brought by PCA3 does not end with detection of cancer but also includes stratification of its significance [47].…”
Section: Prostate Cancer Antigen 3 -Replacing Protein Detection With mentioning
confidence: 99%
See 2 more Smart Citations